Investigação de parâmetros físico-químicos e microbiológicos de qualidade da água de poços no município de Sousa-PB para fins de potabilidade - Mirelly Alexandre Gomes; Emanuel Victor da Silva Ramos; Luís Carlos dos Santos; Damião Júnior Gomes; Antonio José Ferreira Gadelha (Revista Principia, 2018)
Physicochemical and microbiological analyzes of waters from artesian wells offered to the population of the urban area of Sousa-PB. They were carried out in order to verify the potability and suitability for human consumption, according to parameters established by Ordinance nº 2.914 / 2011 of the Ministry of Health. Due to physical-chemical parameters caused mainly, by the high concentration of total dissolved solids, such as: sodium, bicarbonates and chlorides some samples were considered inadequate. It was observed that these parameters did not change much during the months in which they were monitored, indicating that the alternation between rainy and dry periods does not influence the concentration of these chemical species. In addition, contamination by the presence of total coliforms, thermotolerant and E. coli was also observed in all the wells evaluated, which may be associated with clandestine sewage connections or infiltrations caused by septic tanks. Finally, there is an urgent need for a quality control of the water offered to the population of SousaPB, considering that, the alteration of some parameters can cause damages to human health.